PENERAPAN PEMBELAJARAN DARING MATERI PERSAMAAN GARIS LURUS PADA SISWA KELAS VIII MENGGUNAKAN PENDEKATAN SAINTIFIK BERBANTUAN MEDIA VIDEO ANIMASI - Aisyah Azizah; Luvy Sylviana Zanthy (IKIP Siliwangi, 2021)
This research study is a classroom action research which four stages namely planning, implementing, observing, and reflecting in two cycles. This research aims to provide information about the solution of the problems faced by teachers and students in online math learning in the classroom to improve the ability of teachers and students so that several cycles are carried out. This research was conducted on students of class VIII as many as 36 students. The data obtained was presented in two ways, qualitatively and quantitatively. Data were taken from observation and straigh line equation. The results of this research showed that scientific approach with animation video media were effective can increase mathematics learning achievement, the results of the observations showed positivity and good responses from the students. The improvement can be seen by the rise in the students’ mean percentage in the test results: 52% in the first cycle and 82% in the second cycle. The mean difference achievement results from the first cycle test to the second cycle test, which is 30%. Based on the criteria for the success rate of the action, it can be concluded that the quality of mathematics online learning use a scientific approach assisted by animation video in straight line equation subject in very good criteria.